Cooperation Between Indonesia And Taiwan In Supporting The Protection Of Runaway Indonesian Migrant Workers In Taiwan - ANDIANI, Dzulfia; JUNED, Mansur (Journal of Tourism Economics and Policy, 2024)
Indonesia's relations with Taiwan cannot be separated from problems and issues related to Indonesian Migrant Workers. Among these issues is the case of Indonesian Migrant Workers who exceeded the period of stay or overstayed in Taiwan. The overstaying status of Indonesian Migrant Workers creates vulnerability to violations of the rights of Indonesian Migrant Workers and even Indonesian Migrant Workers can be treated arbitrarily. So protection is needed so that the rights of Indonesian Migrant Workers are fulfilled. The type of research that the author will use is qualitative descriptive research because it is considered appropriate to research needs. The data sources used by the author in this research are secondary data such as data obtained from documents, photos, research journals, books relevant to research, news and credible internet media as support for primary sources related to regulations. the rights of Indonesian migrant workers abroad. The results of this research show that the protection and cooperation efforts undertaken to protect Indonesian Migrant Workers include institutional improvements through BP2MI, the launch of the SP2T and Embedded SP2T schemes, the renewal of the Memorandum of Understanding (MoU) between Taiwan and Indonesia regarding the Recruitment, Placement and Protection of Indonesian Migrant Workers in December 2018, as well as a self-surrender program for overstayer workers from the Taiwanese authorities.